Terrorist threats from the maritime domain : Singapore’s response - Quivooij, Romain (2015)
Terrorist threats from the maritime domain are a recurring challenge around South and Southeast Asia even prior to the emergence of actors such as the Islamic State (IS) and Al Qaeda in the Indian Subcontinent (AQIS). Singapore’s position as a hub for maritime trade and industries has required distinct initiatives to mitigate potential threats by terrorist organisations.